PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN CAPITALINTENSITY TERHADAP PENGHINDARAN PAJAK - Daka Sepry Sihombing; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
The purpose of this research was to determine and analyze the effect of corporate social responsibility and capital intensity on the tax avoidance. This research is quantitative and uses secondary data taken from annual reports of transportation and logistic in the transportation sub-sector which exist on Indonesia Stock Exchange (BEI) during the 2017-2020 period. Purposive sampling method is the method that researchers use with a sample of 30 data. The results of this research prove that corporate social responsibility has a negative effect on tax avoidance but capital intensity has a significant effect on tax avoidance. And simultaneously concluded that corporate social responsibility and capital intensity have an effect on tax avoidance.